Bibliometric Analysis of Climate Village Program in Scopus Database by Indonesian Author - Arif Purwantoro; Tri Haryanto; Sri Endah Nurhidayati (Postgraduate, University of Mataram, 2023)
The issue of global warming El Nino is a weather phenomenon in which there is an increase in water surface temperature in the Pacific Ocean which results in significant changes in climate in various regions in the world, including Indonesia. In this study, the traits, well-liked works, writers, and topics connected with the Climate Village initiative are described. Â The purpose of this study is to map and provide a brief overview of the bibliometrics of climate village programs that can be used to examine trends, patterns, and developments. This research uses article publication data sourced from the Scopus database from 2000-2023 with the theme of With the VOSviewer tool, the climate village program or climate village program gathered 60 papers written by Indonesian authors. Â The results showed that articles with the theme of climate village programs by Indonesian authors in the Scopus database were first published in 2014. Articles with the theme of the climate village program were published the most in 2021 (18 documents) while the journal that published the most was Lop Conference Series Earth and Environmental Science. Most journal affiliations are from Universitas Gadjah Mada and Universitas Sebelas Maret. Most journals are published in the United States, India, and Indonesia. The most common subject is Environmental Science. Keywords related to the climate village program include Community, development, resilience, Climate change, strategy, impact, case study, program, Indonesia, and environmental change.